Understanding different motivational mechanisms for downward, lateral, and upward knowledge transfer - Kang, Minhyung; Kim, Byoungsoo (Social Behavior and Personality, 2020)
We applied the theory of planned behavior to examine the relative effects of expected reciprocity, self-efficacy, and subjective norms as antecedents enhancing employees’ downward, lateral, and upward knowledge transfer. Structural equation modeling with partial least squares analysis was used to examine the hypothesized relationships with data gathered through a social network survey from 385 employees in research and development groups in South Korea. Results indicated that self-efficacy was the strongest antecedent of downward knowledge transfer. In lateral knowledge transfer, expected reciprocity showed a significant negative effect. Last, upward knowledge transfer was mainly influenced by self-efficacy and subjective norms. However, subjective norms were positively related to upward knowledge transfer, whereas the relationship between self-efficacy and upward knowledge transfer was negative. These results support the usefulness of the relational approach in understanding the different motivational mechanisms for each of the types of knowledge transfer.
Keywords: Downward knowledge transfer; Expected reciprocity; Lateral knowledge transfer; Self-efficacy; Subjective norms; Upward knowledge transfer